Design and modelling of thin film bulk acoustic resonator (FBAR) for RF application. (2023) - Joshi, P.K.; Bhalotiya, L.H.; Jaiswal, S.W.; Butram, V.W.; Hasamnis, M.A.; Upadhyay, Subrahamanyam
Abstract: Thin film bulk acoustic resonator (FBAR) is widely utilized as an RF filter (Q) in order to achieve minimal in-band losses and high Quality Factor in complex 5G wireless communication systems. This paper describes the basic notion of FBAR on top of a cavity device design for building an RF-filter. The top and bottom electrodes are made of aluminium (Al), the piezoelectric materials used are zinc oxide (ZnO) and barium titanate (BaTiO3 ), and the substrate is silicon (Si). The BaTiO3 -based resonators can function better at high temperatures because BaTiO3 has the highest thermal stability of any piezoelectric material where as ZnO is mostly used to build sensors and actuators due to lower flaws and MEMS compatibility. Also, the resonator attains remarkable Quality factors of 1895 and 1780 for ZnO and BaTiO3 at 5.6 GHz, respectively. A lower rate of energy loss is indicated by a higher quality factor.